Pengaruh Kepuasan Kerja, Gaya Kepemimpinan, dan Budaya Organisasi Terhadap Organizational Citizenship Behavior PT. Ambang Barito Nusapersada Serta Perbedaannya Pada Karyawan Kontrak Dan Karyawan Tetap - Muhammad Tiar; Taharuddin Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
This research aims to test the difference in Organizational Citizenship Behavior (OCB) between permanent and contract employees, continued to test the influence of job satisfaction, leadership style, and organizational culture on OCB employees of PT Ambang Barito Nusapersada. The study used a quantitative approach, with a sample of 27 employees (saturated sampling) divided into 13 permanent employees and 14 contract employees. Questionnaires are used as instruments while Independent sample t-tests and multiple linear regressions to test hypotheses. The results showed permanent and contract employees showed no difference in OCB. Other test results, proving job satisfaction, leadership style and organizational culture simultaneously have a significant effect on OCB, and partially only job satisfaction and organizational culture have a significant effect Keywords: Organizational Citizenship Behavior, OCB, Permanent Employees, Contract Employees, Job Satisfaction, Leadership Style, and Organizational Culture